Effect of some mineral nutrients in growth and some physiological variables in barley plant - Faeza Mahmood; Hussain Mohammed; Farah Salih (College of Education for Pure Sciences, 2007)
Pot experiment was conducted in the wiry house to study the effect of treated soil with boric acid ,magnesium sulphate and calcium chloride with concentrations of (0.1 %,0.2%,0.3%) Kg soil on growth of barley cultivars ( 402) by its effect on shoot and root systems length their dry Veight ,chlorophyll ,carbohydrate ,protein, relative water content of leaves and mineral composition of shoot and root systems. The results shows that treating the soil with calcium chloride lead to enhance the plant growth by increasing shoot length and its dry weight, root length ,leaves content of protein and carbohydrate and also lead to enhance the mineral composition of shoot and root systems by increasing calcium, magnesium, potassium concentrations as compared with the other treatments . Vhile the results showed that when soil treated with boric acid lead to significant decrease in shoot length and dry weight of shoot ,root systems, chlorophyll a,b content of leaves and cell membrane stability and increase in protein concentrations of shoot and root systems by decreasing potassium and magnesium of shoot and root systems as compared with the other treatments.